Sleep quality among non-hospitalized COVID-19 survivors: a national cross-sectional study - Huong Thi Xuan Hoang; Wing Fai Yeung; Quyen Thi Mai Truong; Cuc Thi Le; Cuc Thi Le; Anh Thi My Bui; Quang Vinh Bui; Quyen Thi Le Le; Linh Ha Quach (Frontiers Media S.A., 2024)
ObjectivesInsomnia is a common symptom after COVID-19 infection; however, its current evidence was among hospitalized COVID-19 patients. This study aimed to assess the prevalence of insomnia and identify its association with depression and anxiety among non-hospitalized COVID-19 recovered population.MethodsWe conducted a cross-sectional online survey of 1,056 COVID-19 survivors within 6 months of initial COVID-19 infection and retrieved did not require hospitalization. The Insomnia Severity Index, and Depression Anxiety and Stress Scale-14 were used. Multivariate logistic regression was used to examine the associations between depressive and anxiety score, and participants' insomnia level.ResultsThe prevalence of insomnia was 76.1%, and among those, 22.8% of participants scored for severe insomnia. One third of participants reported worse sleep quality, shorter sleep duration, and harder to fall asleep, half reported more awaken nights after COVID-19 infection. Participants with depressive (OR 3.45; 95%CI 1.87-6.34) or anxiety (OR 3.93; 95%CI 2.52-6.13) had significantly higher odds of developing insomnia. Other risk factors of insomnia included pre-existing chronic conditions and higher education level, while COVID-19 symptoms and duration were not significantly associated.ConclusionOur study highlights the substantial burden of insomnia among non-hospitalized COVID-19 survivors and the significant association of depression and anxiety on the development of this long-term effect of COVID-19. These findings underscore the need for comprehensive interventions that address both sychological and sleeping health in this population.